Workplace bullying in the United States: An analysis of state court cases - Rickey E. Richardson; Reggie Hall; Sue Joiner (Cogent Business & Management, 2016)
Workplace bullying detrimentally impacts the bullied worker, co-workers, and potentially the entirety of the organization in which it takes place. Many nations, other than the United States, have long since recognized this impact and have implemented laws which provide injured parties a means to seek redress of their situations. Since there are no specific independent causes of action to address bullying in the workplace at either the Federal or State level, affected employees in the US face significant legal hurdles when seeking remedies to their situations. However, as evidenced by recent laws enacted by legislatures in Utah, Tennessee, and California and an employment policy enacted by a county in Georgia, a changing tide may be occurring. Court cases referencing workplace bullying have been analyzed in prior research, but there appears to be a gap in the analysis of United States' State court cases consisting of those reported between January 2009 and 31 December 2015. Content analysis was utilized in order to bring research up to date. Injured parties and their legal representatives, as well as employers who are interested in potentially minimizing claims, creating better workplaces, and improving productivity may benefit from the findings of this study.
Keywords: 650